Ainea conzattii (Iridaceae: Tigridieae) revisited: description of a new variety - Martorell, Carlos; López-Ferrari, Ana Rosa; Espejo-Serna, Adolfo; García-Meza, Diego; Clayton, Rupert (Phytotaxa, 2023)
A new variety of Ainea conzattii is described and illustrated, a key to recognize the two varieties of the species and a distribution map of both taxa are included.